On the origin and consequences of racism - Matthew Bonick; Antonio Farfán-Vallespín (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2016)
Using a novel method to measure racism at the individual and country level, we show, our measure of racism has a strong negative and significant impact on economic development, quality of institutions, education and social capital. We test different hypotheses concerning the origin of racism and its channels of impact to establish causality. We find racism is not correlated with measures for the coexistence of different racial or ethnic groups or ethnically- motivated conflicts. Importantly, we show, for former colonies, racism is strongly correlated with the presence of extractive institutions during colonial times, even after controlling for current institutions, GDP per capita and education. We argue, extractive colonial institutions not only had a negative impact on the political and economic institutions but also shaped the cultural values of the population. We claim colonial powers instilled racism among the population of their colonies in order to weaken their ability for collective action.
Keywords: 330; Ethnische Diskriminierung; Kolonialismus; Wirkungsanalyse